2006
DOI: 10.1007/s10162-006-0060-9
|View full text |Cite
|
Sign up to set email alerts
|

Audiological Evaluation of Affected Members from a Dutch DFNA8/12 (TECTA) Family

Abstract: In DFNA8/12, an autosomal dominantly inherited type of nonsyndromic hearing impairment, the TECTA gene mutation causes a defect in the structure of the tectorial membrane in the inner ear. Because DFNA8/12 affects the tectorial membrane, patients with DFNA8/12 may show specific audiometric characteristics. In this study, five selected members of a Dutch DFNA8/12 family with a TECTA sensorineural hearing impairment were evaluated with pure-tone audiometry, loudness scaling, speech perception in quiet and noise,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
39
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(46 citation statements)
references
References 15 publications
7
39
0
Order By: Relevance
“…However, because this change was not present in the controls, it cannot be ruled out that it has an effect on the phenotype of these patients or it may even act synergistically with the T1866M (c.5597C4T) mutation. The similar results with two changes in one family were reported by Plantinga 12 in 2006. The T1866M mutation that we detected in this study was previously reported in one family each in Korea, Spain and the USA.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…However, because this change was not present in the controls, it cannot be ruled out that it has an effect on the phenotype of these patients or it may even act synergistically with the T1866M (c.5597C4T) mutation. The similar results with two changes in one family were reported by Plantinga 12 in 2006. The T1866M mutation that we detected in this study was previously reported in one family each in Korea, Spain and the USA.…”
Section: Discussionsupporting
confidence: 91%
“…In this study, all patients showed typical genotype-phenotype correlations of SNHL with TECTA mutation as previously described. 8,12,15 The family F818 in which the R1773X (c.5318C4T) mutation in the ZA domain was detected, showed high frequency hearing loss that was slowly progressive. The affected proband (Figure 1) noticed bilateral hearing impairment when she was around age 20, and her right hearing level was worse than the left because of cholesteatoma in her right ear.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, there is a difference in the nature of the impairment between the two groups of patients. In presbyacusis, the impairment implies sensorineural hearing loss, whereas in the present patients, it mainly implies intracochlear conductive hearing loss [Plantinga et al, 2007].…”
Section: Discussionmentioning
confidence: 90%
“…Vestibular function was not evaluated because the family members were not willing to undergo the tests. The affected family members also did not wish to undergo further hearing tests, such as acoustic reflex thresholds, loudness discomfort levels, distortion product otoacoustic emissions to test outer hair cell functionality, frequency-modulated pure tones to assess frequency discrimination and speech perception in noise, as described before [Plantinga et al, 2007].…”
Section: Resultsmentioning
confidence: 99%